International Reserves in Low Income Countries : Have they Served As Buffers?. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper provides a historical perspective on the role of international reserves in low-income countries as a cushion against large external shocks over the last three decades - including the current global crisis. The results suggest that international reserves have played a role in buffering external shocks, with the resulting macroeconomic costs varying with the nature of the shock, the economy's structural characteristics, and the level of reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet